Studies on transfer pricing systems and profit shifting: impact of the international regulation on the shifting behaviour of Brazilian firms - Rathke, Alex Augusto Timm (2019)
This study investigates the effect of the transfer pricing (TP) rules on tax-induced profit shifting by firms. It is composed by three parts. The first part analyses the characteristics of TP rules across countries to create a classification of TP systems based on regulatory similarities. Hierarchical clustering method is applied for the analysis of 57 qualitative and quantitative TP characteristics. Results indicate the existence of four distinct TP systems, of which the largest group is composed of countries with TP rules that are consistent with the OECD TP guidelines. The second part analyses the relation between the characteristics of TP rules and the perception of tax enforcement across countries. Current tax research assumes that more extensive tax rules imply in higher tax enforcement, for this study focuses in testing this assumption. Results indicate that different measures for the tax enforcement perception are associated with different characteristics of TP rules. The third part investigates the profit shifting in Brazil and the effect of different TP systems applied to the foreign related parties. The Brazilian context provides a novel case for analysis, since it combines an extreme tax burden, a highly complex tax system, and a unique set of TP rules, thus to represent a relevant set of shifting incentives. As expected, this study finds strong evidences of profit shifting in Brazilian firms. Moreover, results suggest that some rules are more effective in curtailing the profit shifting, but firms are still able exploit vulnerabilities in TP systems towards the shifting strategy